Iridium(III)‐Catalyzed CH Amidation of Arylphosphoryls Leading to a P‐Stereogenic Center. Issue 39 (21st August 2014) - Gwon, Donghyeon; Lee, Donggun; Kim, Jiyu; Park, Sehoon; Chang, Sukbok
Abstract Direct CH amidation of arylphosphoryl compounds has been developed by using an IrIII catalyst system under mild conditions. A wide range of substrates could be employed with high functional‐group tolerance. This procedure was successfully applied for the first time to the asymmetric reaction giving rise to a P‐chirogenic center with a high diastereomeric ratio of up to 19:1 (90 % de).